AKIBAT HUKUM PENGAMBILALIHAN SAHAM PERSEROAN TERBATAS YANG TIDAK MELAKUKAN PENGUMUMAN SURAT KABAR BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - Tafwan, Jihan; Firdaus, Firdaus; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Takeover is a legal act carried out by a legal entity or an individual person to take over the Company's shares resulting in the transfer of control over the Company. Article 127 paragraph (2) instructs the directors of the Company to announce a draft summary at least in 1 (one) newspaper that will take over no later than 30 (thirty) days prior to the invitation of the General Meeting of Shareholders. Because with this announcement, all parties interested in the company know that a new shareholder will be held.The purpose of this study was to determine the implementation of the takeover of shares of a Limited Liability Company according to Law Number 40 of 2007 concerning Limited Liability Companies. And to find out the legal consequences of Limited Liability Companies that take shares without making newspaper announcements. This type of research can be classified in the type of normative juridical research that is research conducted by examining literature discussion with secondary data sources consisting of primary legal material in the form of statutory regulations, secondary legal materials legal books, and tertiary legal materials in the form of dictionaries. Then the data were analyzed qualitatively by analyzing descriptive data obtained from secondary data.Conclusions that can be drawn, First, acquisition of shares can be done in 2 (two) ways, namely through the directors of the Company and can be directly from shareholders. If the takeover has passed the procedures stipulated by the Company Law, then the acquisition of shares can be said to be valid and can be legally accounted for. Second, As a result of the Legal takeover of shares that do not carry newspaper news is null and void. Since the first time the share acquisition agreement was made, it has been invalid, so the law considers that the agreement to take over the shares has never existed before.Keywords: Legal Consequences - Share Acquisition - Companies Not Announcing Newspaper